THE IMPLEMENTATION OF PUBLIC SERVICES IN THE SMART KAMPUNG PROGRAM THROUGH THE SIMAS MANDIRI INNOVATION : (A Study on Public Services in Genteng Kulon Village, Genteng District, Banyuwangi) - AKYUNI ISLAMI; Dimas Imaniar; Niko Pahlevi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Genteng Kulon Village leads in public service innovation with its Simas Mandiri program, a technological breakthrough acknowledged and awarded by the Banyuwangi Regent in 2019. Simas Mandiri's initial success was bolstered by adequate resources, encompassing essential hardware (self-service machines, computers, networks), integrated software, and crucial supporting infrastructure for efficient operations. However, Simas Mandiri hasn't reached its full potential due to several challenges. In communication, current socialization efforts are ineffective, as residents still prefer manual services, indicating a need for more impactful strategies. Concerning technology resource management, hardware quality has significantly degraded and failed over time, highlighting an urgent need for routine oversight and proactive maintenance. Additionally, an ambiguous and informal bureaucratic structure causes confusion in task distribution and responsibilities, impeding coordination and accountability. Therefore, to ensure Simas Mandiri's optimal performance and sustainability, strategic improvements are vital in communication approaches, technology asset management, and establishing a more structured bureaucracy.